Encouraging social entrepreneurship development in creative arts school in Malaysia - Amaran, Mazdan Ali; Lim Hock Eam, Hussin Abdullah, (Opción, 2020)
The study aims to investigate encouraging social entrepreneurship development in a creative arts school in Malaysia via comparative qualitative research methods. As a result, activities organized by the creative arts faculty can be classified into 2 programmes, entrepreneurial development and community programmes that have the potential to be developed as social entrepreneurship. In conclusion, as social entrepreneurship is relatively new at the arts faculty level, their knowledge of social entrepreneurship is quite limited and requires greater exposure.